Metode Pembelajaran Pendidikan Agama Islam Pada Generasi Milenial - Nike Namira Susanti; Mislaina Panjaitan; Muhammad Fadly Manurung (Najah Bestari, 2026)
The development of information and communication technology has shaped the characteristics of the millennial generation to be different in the learning process, including in Islamic Religious Education (PAI). The millennial generation tends to be close to digital technology, critical and rational, and prefers interactive, visual, and collaborative learning. This condition requires adjustments in PAI learning methods to be more relevant and effective. This study aims to analyze the characteristics of the millennial generation in PAI learning, the implementation of appropriate PAI learning methods, the role of PAI teachers in applying innovative learning methods, as well as the impact of these learning methods on the attitudes and behavior of the millennial generation. The results of the study show that student-centered PAI learning methods, such as discussions, problem-based learning, project-based learning, and the use of digital technology, can increase activeness, understanding, as well as The internalization of Islamic values. Islamic Education (PAI) teachers play a strategic role as designers, facilitators, motivators, and role models in creating innovative and meaningful learning. The implementation of appropriate PAI learning methods has a positive impact on religious attitudes, social behavior, critical thinking, and the tolerance of the millennial generation. Thus, innovative, participatory, and contextual PAI learning methods become key in shaping a millennial generation that is faithful, virtuous, and capable of facing the challenges of modern life